2010
DOI: 10.1113/expphysiol.2010.052597
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic experimentation on astrocytes

Abstract: We briefly review the current literature where optogenetics has been used to study various aspects of astrocyte physiology in vitro and in vivo. This includes both genetically engineered Ca 2+ sensors and effector proteins, such as channelrhodopsin. We demonstrate how the ability to target astrocytes with cell-specific viral vectors to express optogenetic constructs helped to unravel some previously unsuspected roles of these inconspicuous cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 66 publications
0
52
0
2
Order By: Relevance
“…All these effects could change the activities of astrocytes and regulate the release of gliotransmitters. Indeed, it has been reported that the activation of ChR2 triggers ATP release from ChR2-expressing astrocytes resulting from the elevation of [Ca 2+ ] i (Gourine et al, 2010;Figueiredo et al, 2011;Chen et al, 2013). Astrocytes can release glutamate through Ca 2+ -dependent and -independent mechanisms (Haydon and Carmignoto, 2006;Malarkey and Parpura, 2007).…”
Section: Depolarizing Actuators Control Astroglial Release Of Atp Andmentioning
confidence: 98%
“…All these effects could change the activities of astrocytes and regulate the release of gliotransmitters. Indeed, it has been reported that the activation of ChR2 triggers ATP release from ChR2-expressing astrocytes resulting from the elevation of [Ca 2+ ] i (Gourine et al, 2010;Figueiredo et al, 2011;Chen et al, 2013). Astrocytes can release glutamate through Ca 2+ -dependent and -independent mechanisms (Haydon and Carmignoto, 2006;Malarkey and Parpura, 2007).…”
Section: Depolarizing Actuators Control Astroglial Release Of Atp Andmentioning
confidence: 98%
“…Given the lack of success for novel therapies targeting neuronal entities, it is perhaps surprising that to date few astrocyte targets have been identified. Advances in technology have increased our understanding of astrocytes and their interactions (255), which is still limited by poor astrocyte-specific markers which lack the robust nature of neuronal markers (5). The publication of the astrocytic transcriptome (24) revealed potential new cellular biomarkers that provide tools for generating specific therapeutic approaches to target astrocytes for the purpose of reducing neurodegeneration in AD.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…ChR2 expression in primary cardiac fibroblasts was stable, persisting for at least 6 weeks, without detrimental effects to cell viability and proliferation (Yu et al, 2013). This is in contrast to severe negative effects and cell death reported in astrocytes when high viral titers > 10 11 transducing units/ml of AAV–sGFAP–ChR2 were used (Figueiredo et al, 2011). …”
Section: Cell-specific Optogenetic Targeting In the Heart And Its mentioning
confidence: 91%